2/3(x-6)-1/3(x-3)

Simple and best practice solution for 2/3(x-6)-1/3(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3(x-6)-1/3(x-3) equation:


x in (-oo:+oo)

(2/3)*(x-6)-((1/3)*(x-3)) = 0

(2/3)*(x-6)+(-1/3)*(x-3) = 0

2/3*(x-6)-1/3*(x-3) = 0

2/3*(x-6)-1/3*(x-3) = 0

1/3*x-3 = 0

1/3*x-3 = 0

1/3*x-3 = 0 // + 3

1/3*x = 3 // : 1/3

x = 3/1/3

x = 9

x = 9

See similar equations:

| -2(8u-7)+4v=2(v+6) | | 2w^3+6w^2-4w=0 | | 90d=2 | | -(3-3n)=4(7+2n)+4 | | 81+2d= | | -2n+8(n-7)=-86 | | 6a^3-12a^2+14a=0 | | -3(2-1)=12 | | -2n+8(n-7)=-3-5(v+8) | | 18=69-24 | | L=b+c-dsolvec | | 10w+10+3w=6(9+w)-14 | | 8+7n-6-4n=n-8 | | (2x^2-13x+6)/(6x^2-x-1) | | 8x-9=41 | | 3m(m+4)=18 | | 6x-3=7x-10 | | 1/3(3x-2)=6-x | | 2n+3+8=1 | | 31.83D=5103 | | 1=1+n-1 | | -3y+2x=6 | | 2a-7=-2a+5 | | 291-13-8= | | 0=-4b-6b | | 291-(-13-8)= | | 291-(-13+-8)= | | r/4-7/4+3r/4=1/4 | | -7(3+v)=-77 | | s/5=-16 | | 28x^2-27x-10=0 | | 4-8n=-92 |

Equations solver categories